Lipoprotein concentration in patients requiring extracorporeal membrane oxygenation - Sébastien Tanaka (Nature Portfolio, 2021)
Abstract Extracorporeal membrane oxygenation (ECMO), a relevant technology for patients with acute respiratory distress syndrome (ARDS) or acute cardiac failure (ACF), is a frequent cause of systemic inflammatory response syndrome. During sepsis, HDL cholesterol (HDL-C) and LDL cholesterol (LDL-C) concentrations decrease, and an association between low lipoprotein levels and poor outcomes was reported. There are no data from patients undergoing ECMO. The goal of this study was to characterize the lipoprotein profiles of ICU patients requiring ECMO. All consecutive patients admitted for ARDS or ACF requiring ECMO were prospectively included. Daily lipoprotein levels and short-term prognosis outcome were assessed. 25 patients were included. On admission, lipoprotein concentrations were low, under the reference values ([HDL-C] = 0.6[0.4–0.8]mmol/L;[LDL-C] = 1.3[1.0–1.7]mmol/L). A statistically significant rise in lipoproteins overtime was observed during the ICU stay. We found no relationship between lipoproteins concentrations and mortality on Day-28 (p = 0.689 and p = 0.979, respectively). Comparison of surviving patients with non-surviving patients did not reveal any differences in lipoproteins concentrations. Stratification between septic and non-septic patients demonstrated that septic patients had lower lipoproteins concentrations on admission (HDL-C: 0.5[0.3–0.6]mmol/l vs 0.8[0.6–0.9]mmol/l, p = 0.003; LDL-C: 1.1[0.9–1.5]mmol/l vs 1.5[1.3–2.6]mmol/l; p = 0.012), whereas these two groups were comparable in terms of severity and outcomes. HDL-C concentrations during ICU hospitalization were also significantly lower in the septic group than in the non-septic group (p = 0.035). In conclusion, Lipoprotein concentrations are low in patients requiring ECMO but are not associated with poor outcomes. The subpopulation of septic patients had lower lipoprotein levels overtime, which reinforces the potential key-role of these particles during sepsis.